Peran Guru dalam Perspektif Sosiologi Pendidikan - Fathoni Imam, Ratu Bilkis; Tantowi, Nanang; Yuniarto, Bambang; Mulyana, Asep (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2022)
The purpose of this paper is to describe the sociology of education in Islam as well as the duties and responsibilities of teachers in the perspective of the sociology of education. The approach used is qualitative by using library research method (library study). The main data sources in this paper are books or scientific journals on the sociology of education, while the secondary sources are books or other relevant articles. Data analysis uses content analysis techniques. Data analysis was carried out in stages: data presentation, data filtering, classification, and drawing conclusions. The results of the study from this paper are: (1) The teacher is an element of education that has a very important role; (2) The duties and responsibilities of teachers in the sociological review of education include activities in schools and the community. Keywords: Teacher, Education, Sociology.